METODE PEMBELAJARAN SQ3R TERHADAP KETERAMPILAN MEMBACA KRITIS TEKS EKSPOSISI SISWA KELAS V SD - Sukma Prischayani, Belliana; Ira Eko Retnosari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low critical reading skills are the main background of this research, especially in expository texts and the inaccurate use of learning methods. As an alternative to improve critical reading skills, the SQ3R method (Survey, Question, Read, Recite, Review) is the best method chosen because it actively involves students during implementation so they can understand what has been read. This study aims to determine the effect of the SQ3R learning method on students' critical reading skills in expository texts. This research design uses a quantitative research type with a quasi-experimental research method. Non-equivalent pretest-posttest control group design was chosen as the research design by involving two classes, namely the experimental class (class V A students) and the control class (class V B students) at SDN Dukuh Menanggal 01/424 Surabaya. Data were collected through the results of the pre-test and post-test which included 10 essay questions. The analysis techniques used were normality test, homogeneity test, and Independent Sample T-Test based on SPSS 25. The study resulted in a statement that the SQ3R learning method has an influence on students' critical reading skills with 0.000 <0.605 as a demonstration of significance value. Comparison of posttest scores between the experimental class with a value of 73.26 while the control class was 47.5 resulting in a difference of 25.76, it can be proven that there is an influence of the SQ3R learning method on critical reading skills of expository texts of fifth grade elementary school students.